Mechatronics and machine vision 2003 : future trends - Billingsley, J. (John) (Robotics and mechatronics series ;, 2003)
This book presents a specially edited selection of papers from the 10th Annual Conference of Mechatronics and Machine Vision in Practice(M2VIP 2003), which provides a forum for international experts and researchers to present and review advances in Mechatronics and Machine Vision. The conference was held in Perth,Australia, 9-11 December 2003.